Antibiotic Therapy for Chorioamnionitis to Reduce the Global Burden of Associated Disease - Johnson, Clark T.; Adami, Rebecca R.; Farzin, Azadeh (Frontiers in Pharmacology, 2017)
Chorioamnionitis is associated with significant maternal and neonatal morbidity and mortality throughout the world. In developed countries, great progress has been made to minimize the impact of chorioamnionitis, through timely diagnosis and appropriate treatment. In the global setting, where many women deliver outside the healthcare facilities, this diagnosis is frequently overlooked and not properly treated. In addition to its impact on maternal health, a significant proportion of neonatal morbidity and mortality can be prevented by both recognition and access to readily available treatment. With the increasing focus on saving the most vulnerable members of society, we echo the need for providing parturient women with suspected chorioamnionitis universal access to appropriate therapy. We describe known effective antibiotic therapies for chorioamnionitis and provide an overview of additional potential antimicrobial treatments that might be effectively implemented in areas with limited access to care.